Representasi Komunikasi Keluarga dalam Film “Sejuta Sayang Untuknya” - Muhammad Pradika Ikbal Firdaus; Dedeh Fardiah (Bandung Conference Series: Public Relations, 2023)
Abstract. Representation of a film “My Million For Her” is the focus of this research. The film focuses on this family conflict as an entity in understanding the meaning of real life. The semiotic analysis of Roland Barthes on Herwin Novianto's film "A Million of His Love" aims to analyze the communication patterns carried out by Gina's father to his son by knowing the three levels of meaning in analyzing a film, namely the meaning of denotation, the significance of connotation and the myths that are present in the film. As well as how a film conveys a moral message that can be applied in everyday life and has important values with the hope of being able to motivate and refer to the social reality in society. This method of research uses the method of qualitative investigation using the semiotic analysis of Roland Barthes in which Barthes analyzes the three levels of meaning: denotation, significance of connotation, and myths and communication patterns that occur within the family on the film scene. The results of the research from the film "Million Love to Her" is to love each other, take care of each other and give each other the best in communication father and Ghina who is always communicative at every problem makes Gina a good and intelligent child. The meaning of Denotation in the movie scene is a hard-working father. The meaning of connotation is a father who is a hard-working figure who endeavors all forms of affection to his child, especially in the field of education where it is a hope of the father for his child to get a higher education in order to be a successful child. Both meanings are also supported by myths that give justification through the values of life, culture, customs that exist in the circle at a certain time. Abstrak. Representasi sebuah film “Sejuta Saya Untuknya” merupakan fokus penelitian ini. Film yang memfokuskan pada konflik keluarga ini sebagai wujud dalam memahami arti dari kehidupan sesungguhnya. Analisis semiotika Roland Barthes pada film Sejuta Sayang Untuknya karya Herwin Novianto bertujuan untuk menganalisis lebih dalam pola komunikasi yang dilakukan oleh ayah Gina kepada anaknya dengan mengetahui 3 tingkatan makna dalam menganalisis sebuah film yaitu makna denotasi, makna konotasi dan mitos yang terdapat pada film Sejuta Sayang Untuknya. Serta bagaimana sebuah film menyampaikan pesan moral yang dapat diaplikasikan dalam berkehidupan sehari-hari dan memiliki nilai-nilai yang penting dengan harapan mampu memotivasi dan mengacu pada realitas sosial dalam masyarakat. Metode penelitian ini menggunakan metode penelitan kualitatif dengan menggunakan analisis semiotika Roland Barthes yang mana Barthes menganalisis 3 tingkatan makna yaitu mokna denotasi, makna konotasi, dan mitos dan pola komunikasi yang terjadi didalam keluarga pada adegan film Sejuta Sayang Untuknya. Hasil penelitian dari film “Sejuta Sayang Untuknya” yaitu saling menyayangi, saling menjaga, saling memberikan yang terbaik dalam komunikasi ayah dan Ghina yang selalu komunikatif disetiap permasalahan menjadikan Gina anak yang baik dan cerdas. Makna Denotasi yang terdapat dalam scene film tersebut adalah seorang ayah yang bekerja keras. Makna Konotasi ialah seorang ayah yang merupakan sosok pekerja keras yang mengusahakan segala bentuk kasih sayang kepada anaknya, terutama pada hal Pendidikan dimana hal tersebut adalah sebuah harapan sang ayah agar anaknya mendapatkan sebuah Pendidikan setinggi-tingginya agar menjadi anak yang sukses. Dari kedua makna tersebut juga didukung oleh mitos yang memberikan pembenaran melalui nilai-nilai berkehidupan, budaya, adat yang ada didlam lingungan pada kurun waktu tertentu.